The Problem of Private Economy in the Ancient Near East - Vargyas, Péter
ersch. 1988; Besprechungsartikel von Archi, A. (Ed.), Circulation of Goods in Non-Palatial Context in the Ancient Near East (Incunabula Graeca, 82. 1984).